2019
DOI: 10.31557/apjcp.2019.20.3.683
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Women with “Atypical Squamous Cells Cannot Exclude High-Grade Squamous Intraepithelial Lesion” (ASC-H) Smears

Abstract: Objectives:To evaluate prevalence of underlying significant pathologies among women with cervical smears rated as ‘atypical squamous cells cannot exclude high grade squamous intraepithelial lesion (ASC-H)’, as well as associated risk factors.Methods:Medical records were reviewed of all consecutive women with ASC-H smears who had undergone colposcopy at Srinagarind Hospital from January 2008 to July 2016. Significant pathology results included cervical intraepithelial neoplasia (CIN) 2-3, adenocarcinoma in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In this context, additional HR HPV testing in women over 40 years of age with ASC-H cytology was considered particularly helpful in identifying significant dysplasia [ 35 ] and a reasonable option for triage [ 37 ]. In contradiction with the findings addressed above [ 17 , 35 , 37 , 38 , 39 , 40 ], patient age was not identified as a significant predictor of CIN2+ in our analysis, as described in the results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this context, additional HR HPV testing in women over 40 years of age with ASC-H cytology was considered particularly helpful in identifying significant dysplasia [ 35 ] and a reasonable option for triage [ 37 ]. In contradiction with the findings addressed above [ 17 , 35 , 37 , 38 , 39 , 40 ], patient age was not identified as a significant predictor of CIN2+ in our analysis, as described in the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have identified age as an important factor in disease outcome in ASC-H patients, showing that younger women are more likely to display CIN2+ lesions than older patient groups [ 17 , 35 , 37 , 38 , 39 , 40 ]. Furthermore, it was demonstrated that in patients with ASC-H cytology, there is an age-dependent HR HPV positivity that is exceptionally high in younger patients and decreases with age [ 35 , 37 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…No association was found between the likelihood of HSIL and patient age (under vs over 40 years old) in our study. Studies have demonstrated that younger women have an increased risk of HSIL after referral with LBC/pap smear demonstrating ASC‐H/pHSIL 5,6,8,24 . The renewed NCSP screens women from the age of 25, whereas women were previously screened from the age of 18.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that women with pHSIL be referred for colposcopy due to the likelihood of HSIL being found, with 12.2–65.6% of pHSIL cytology being found to have HSIL at colposcopy or on histology in international studies 5–11 . In Australia, an Australian Institute of Health and Welfare study 2 showed that in 2015, 38.4% of total pHSIL cytology results were found to have histologically confirmed HSIL, and 0.4% to have SCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation